2013
DOI: 10.1007/s11864-013-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapy and Future Directions in Biliary Tract Malignancies

Abstract: OPINION STATEMENT Cancers of the biliary tree represent a rare group of diseases with a devastating impact on patients. Gallbladder cancer is often associated with cholelithiasis. Cholangiocarcioma may arise in the setting of biliary inflammation such as primary sclerosing cholangitis but most commonly occurs in patients without a particular risk factor. Surgical removal of biliary cancer is essential for cure, but it is associated with a very high rate of recurrence and for many patients is not possible at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…There are about 14,000 new cases per year in the United States (1,2). Most cases of BTC are lethal due to advanced disease at presentation or high relapse rate after local treatment (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…There are about 14,000 new cases per year in the United States (1,2). Most cases of BTC are lethal due to advanced disease at presentation or high relapse rate after local treatment (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…As such, these symptoms are difficult to treat and exhibit a poor prognosis ( 1 4 ). A previous study has reported the overall five-year survival rate following radical resection to be 15–50%, as cholangiocarcinoma cells easily metastasize, resulting in relapse ( 5 ). The formation of cholangiocarcinoma often proceeds through several steps, including interaction among the cancer-promoting environmental factors, oncogene activation and tumor-suppressor gene inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…The level of γ-glutamyltransferase (1.13–3.5 µkat/L) was the only elevated parameter in all five patients. Elevation in γ-glutamyltransferase levels is often seen in patients with colorectal carcinoma with liver metastasis [ 37 ] or in patients with biliary tract diseases including malignancies [ 38 ]. All liver samples were also scored by the pathologist for steatosis (score of 0–1) and fibrosis (score of zero), and the obtained scores indicate no or mild signs of liver disease in patients’ biopsies.…”
Section: Discussionmentioning
confidence: 99%